A proposal for a visual speech animation system for European Portuguese - Serra, J.; Ribeiro, M.; Freitas, J.; Orvalho, V.; Dias, M. S. (Advances in Speech and Language Technologies for Iberian Languages. Communications in Computer and Information Science, 2012)
Visual speech animation, or lip synchronization, is the process of matching speech with the lip movements of a virtual character. It is a challenging task because all articulatory movements must be controlled and synchronized with the audio signal. Existing language-independent systems usually require fine tuning by an artist to avoid artefacts appearing in the animation. In this paper, we present a modular visual speech animation framework aimed at speeding up and easing the visual speech animation process as compared with traditional techniques. We demonstrate the potential of the framework by developing the first automatic visual speech automation system for European Portuguese based on the concatenation of visemes. We also present the results of a preliminary evaluation that was carried out to assess the quality of two different phoneme-to-viseme mappings devised for the language.